Baryon-number-violating nucleon decays in sterile neutrino effective field theories - Tong Li; Michael A. Schmidt; Chang-Yuan Yao (Journal of High Energy Physics)
Abstract The search for baryon-number-violating (BNV) nucleon decay provides an in- triguing probe of new physics beyond the Standard Model (SM). Future neutrino experiments will improve the sensitivity to BNV nucleon decays and can serve to search for dark particles. In this work, we study the sterile neutrino effective field theories (EFTs) with baryon number violation and the impact of light sterile neutrino on BNV nucleon decays. We revisit the dimension-6 and dimension-7 EFT operator bases with |∆(B − L)| = 2 or |∆(B − L)| = 0. They are then matched to the baryon chiral perturbation theory. We obtain the effective chiral Lagrangian at low energies and the BNV interactions between the sterile neutrino and baryons and mesons. The rates of nucleon decay to SM neutrinos or a sterile neutrino are calculated. We then show the constraints on the ultraviolet scale from nucleon decay search at Super-K. The correlation of two EFT operators and the dependence on the sterile neutrino mass are also investigated.